Safety, efficacy, and pharmacokinetics of single-tablet elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide in virologically suppressed, HIV-infected children: a single-arm, open-label trial. (September 2017) - Natukunda, Eva; Gaur, Aditya H; Kosalaraksa, Pope; Batra, Jagmohan; Rakhmanina, Natella; Porter, Danielle; Shao, Yongwu; Zhang, Heather; Pikora, Cheryl; Rhee, Martin S
Summary: Background: No once-daily single-tablet regimen is available for HIV-infected children under 12 years. The single-tablet, fixed-dose combination of elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide is a once-daily, integrase strand transfer inhibitor-based regimen approved in the USA and European Union for individuals aged 12 years or older. In this study, we aimed to assess the pharmacokinetics, safety, and efficacy of this regimen in virologically suppressed, HIV-infected children. Methods: In this single-arm, open-label trial, we enrolled virologically suppressed, HIV-infected children from five hospital clinics in Uganda, the USA, and Thailand. Eligible participants were aged 6–11 years, weighed 25 kg or more, had virological suppression (<50 copies of HIV-1 RNA per mL) on a stable regimen for at least 6 months, CD4 count of more than 100 cells per μL, and no history of resistance to elvitegravir, emtricitabine, tenofovir alafenamide, or tenofovir. All participants received the available fixed-dose oral formulation of elvitegravir 150 mg, cobicistat 150 mg, emtricitabine 200 mg, and tenofovir alafenamide 10 mg once per day. Primary outcomes were the pharmacokinetic parameters area under the curve (AUC) concentration at the end of the dosing interval (AUCtau ) for elvitegravir and the AUC from time zero to the last quantifiable concentration (AUClast ) of tenofovir alafenamide, treatment-emergent serious adverse events, and all treatment-emergent adverse events. Results from baseline to week 24 are reported, unless specified otherwise. Primary and safety analyses included all enrolled participants who received one dose of study drug. This study is registered withClinicalTrials.gov, numberNCT01854775 . Findings: Between July 27 and Sept 28, 2015, we screened 26 children, of whom 23 were enrolled and initiated treatment. Median age was 10 years (IQR 8–11), median weight was 30·5 kg (IQR 27·5–33·0), and all participants had virological suppression. The mean AUCtau of elvitegravir was 33 814 ng × h/mL (coefficient of variation 58%), and the mean AUClast of tenofovir alafenamide was 333 ng × h/mL (45%). Exposures to elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide were higher, but modestly so, than those previously reported in adults. All 23 participants tolerated the regimen well; there were no serious adverse events or adverse event-related discontinuations. All participants maintained virological suppression (HIV-1 RNA <50 copies per mL) at week 24. CD4 count decreased by a median of −130 cells per μL (range −472 to 266) with little change in CD4 cell percentage (−2·1%, range −8·4 to 5·9). Interpretation: The fixed-dose combination of elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide was efficacious and well tolerated in virologically suppressed, HIV-infected children. Although plasma exposure of all components was higher than has been reported in adults, there were no safety concerns and the overall bone and renal safety profile was favourable. These data support the use of this regimen in children at least 25 kg in weight. Funding: Gilead Sciences.